1981
DOI: 10.1017/s0022172400069011
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal antibodies in patients with burn injuries

Abstract: SUMMARYSerum samples from 14 patients whose burns had become infected with streptococci of groups A (11 patients), C (one patient) or G (two patients), and from 19 burned patients without bacteriological evidence of streptococcal infection were examined for anti-streptococcal antibodies. Tests were made for anti-streptolysin O (ASO), anti-hyaluronidase (AH), anti-deoxyribonuclease B (anti-DNAase B) and antibody against M-associated protein (MAP). Sera from the patients with streptococcal infections were also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Using five strains of group A streptococci (S. pyogenes), Wannamaker and coworkers (17,18) showed that four immunologically and electrophoretically distinct extracellular DNases, designated DNases A, B, C, and D, are produced and that the relative amount of each enzyme produced varies in these strains. From the clinical viewpoint, DNase B is believed to be the most significant DNase because a high antibody response to it has been demonstrated in the sera of patients infected with group A streptococci (1,2,5,8,15,19). However, it remains uncertain whether the production of DNase B is a common property of group A streptococci and whether multiple DNase produced within the same species are homogeneous, because few studies on their extracellular DNase have been reported and in these only a small number of clinical isolates were used.…”
mentioning
confidence: 99%
“…Using five strains of group A streptococci (S. pyogenes), Wannamaker and coworkers (17,18) showed that four immunologically and electrophoretically distinct extracellular DNases, designated DNases A, B, C, and D, are produced and that the relative amount of each enzyme produced varies in these strains. From the clinical viewpoint, DNase B is believed to be the most significant DNase because a high antibody response to it has been demonstrated in the sera of patients infected with group A streptococci (1,2,5,8,15,19). However, it remains uncertain whether the production of DNase B is a common property of group A streptococci and whether multiple DNase produced within the same species are homogeneous, because few studies on their extracellular DNase have been reported and in these only a small number of clinical isolates were used.…”
mentioning
confidence: 99%